Hidden association of knee-related disability with physical activities among community-dwelling older male Saudi Arabians with knee osteoarthritis (Journal of Health Sciences, 2022)
Introduction: The impact of knee osteoarthritis (OA) on physical activities of daily life was studied extensively among the elderly across the globe but not well understood in the Saudi Arabian populace with cultural consideration. This paper assessed the association between knee flexion range of motion (ROM) and ritual physical activities among elderly males due to knee OA.Methods: A cross-sectional study with a sample of 139 males aged 56–74 years diagnosed with knee OA recruited at prayer places. The subjective evaluation was carried using a disease-specific Arabic knee physical functional questionnaire Knee injury and OA Outcome Score-Physical Function Short form (KOOS-PS), and the anthropometric measure of knee flexion ROM was objectively measured by a manual goniometer.Results: The mean and standard deviation of the study sample age, height, weight, and body mass index were 66.9 ± 4.09 years, 158.4 ± 6.1 cm, 74.6 ± 7.1 kg, and 29.6 ± 1.9 kg/m2, respectively. The mean, standard deviation and median of the knee flexion ROM and Arabic-KOOS-PS Questionnaire score were 100.7 ± 7.9, 101.5 and 12.9 ± 13.7, 13.4. The non-parametric Spearman correlation coefficient between the knee stiffness and KOOS-PS physical activities resulted very strong positively correlation, r = 0.967.Conclusion: A strong positive correlation has been found between hidden knee disability and ritual physical activities among male cohorts in Saudi cultural community with knee OA